Acute Methotrexate Toxicity: A Fatal Condition in Two Cases of Psoriasis - Pankti Jariwala; Vinay Kumar; Khyati Kothari; Sejal Thakkar; Dipak Dayabhai Umrigar (Case Reports in Dermatological Medicine)
We describe two fatal cases of low dose methotrexate (MTX) toxicity in patients with psoriasis, emphasizing the factors that exacerbate MTX toxicity. The first patient was a 50-year-old male of psoriasis on intermittent treatment with MTX. After a treatment-free period of six months, he had self-medication of MTX along with analgesic for joint pain for one week which followed ulceration of the lesions, bone marrow suppression, and eventually death. The second patient was a 37-year-old male of psoriasis, who has taken MTX one week earlier without prior investigations. He had painful ulcerated skin lesions and bone marrow suppression. On investigations, he showed high creatinine level and atrophied, nonfunctioning right kidney on ultrasonography. In spite of dialysis, he succumbed to death. MTX is safe and effective if monitored properly, but inadvertent use may lead to even death also. Prior workup and proper counseling regarding the drug interactions as well as self-medication should be enforced.